Term Neonatal Complications During the Second Localized COVID-19 Lockdown and Prolonged Premature Rupture of Membranes at Home Among Nulliparas With Reference Interval for Maternal C-Reactive Protein: A Retrospective Cohort Study - Geng, Yang; Zhao, Weihua; Liu, Wenlan; Tang, Jie; Zhang, Hui; Ke, Weilin; Yao, Runsi; Xu, Ji; Lin, Qing; Li, Yun; Huang, Jianlin (Frontiers in Pediatrics, 2022)
Objective: The COVID-19 lockdown extended premature rupture of membranes (PROM) expectant time among nulliparas and increased the risk of term neonatal complications. This study investigated the impact of term nulliparas with PROM delays at home on neonatal outcomes during the COVID-19 lockdown period, considering the clinical diagnostic application of maternal C-reactive protein (CRP). Methods: This study collected 505 term nulliparous women who underwent PROM at home from five provinces in a non-designated hospital of China in 2020. We analyzed PROM maternal information at home and neonatal complications in the COVID-19 regional lockdown and compared related information in the national lockdown. Poisson regression models estimated the correlation of PROM management at home, maternal CRP, and neonatal morbidity. We constructed two diagnostic models: the CRP univariate model, and an assessed cut-off value of CRP in the combined model (CRP with PROM waiting time at home). Results: In the regional lockdown, PROM latency at home and the severity of neonatal complications were extended and increased lower than in the nationwide lockdown, but term neonatal morbidity was not reduced in the COVID-19 localized lockdown. Prolonged waiting time at home (≥8.17 hours) was associated with increasing maternal CRP values and neonatal morbidity (aRRs 2.53, 95% CI, 1.43 to 4.50, P for trend <0.001) in the regional lockdown period. In the combined model, CRP ≥7 mg/L with PROM latency ≥8.17 hours at home showed higher diagnostic sensitivity and AUC than only CRP for initial assessing the risk of adverse neonatal complications in COVID-19 regional lockdowns (AUC, 0.714 vs. 0.534, sensitivity, 0.631 vs. 0.156). Conclusion: The impact of the acute COVID-19 national blockade on the PROM newborns' health could continue to the COVID-19 easing period. Maternal CRP reference interval (≥7 mg/L) would effectively assess the risk of term neonatal morbidity when nulliparas underwent prolonged PROM expectant at home (≥8.17 hours) during the second COVID-19 lockdown.